1991
DOI: 10.1007/bf00238438
|View full text |Cite
|
Sign up to set email alerts
|

Effects of premature weaning and diet on lung growth and appearance of adenylate cyclase activator in rat lung

Abstract: Early weaning of rat pups on day 16 to semi-ground Purina chow food and drinking water, ad libitum, delayed growth of body and lungs, and the appearance of adenylate cyclase activator (ACA) in lung after day 22. However, early weaning of pups to either milk or a gel diet containing semi-ground Purina chow food, agarose gel, water (30:1:69, w/w), and drinking water, restored lung and body growth and the appearance of ACA to control values. Early weaning of pups to dry semi-ground Purina chow food and drinking w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…LW/BW ratio in Foxa1 Ϫ/Ϫ mice was similar to that in Foxa1 ϩ/ϩ mice. Previous studies showed that caloric restriction causes a delay in lung morphogenesis, with more prominent effects observed during phases of growth and differentiation (23,30,35). Although surfactant phospholipid content was reduced, surfactant composition was normal in lungs of calorie-deprived animals before birth or during adulthood (8,23).…”
Section: Foxa1mentioning
confidence: 98%
“…LW/BW ratio in Foxa1 Ϫ/Ϫ mice was similar to that in Foxa1 ϩ/ϩ mice. Previous studies showed that caloric restriction causes a delay in lung morphogenesis, with more prominent effects observed during phases of growth and differentiation (23,30,35). Although surfactant phospholipid content was reduced, surfactant composition was normal in lungs of calorie-deprived animals before birth or during adulthood (8,23).…”
Section: Foxa1mentioning
confidence: 98%